Ecopedagogia: uma nova pedagogia com propostas educacionais para o desenvolvimento sustentável/Ecopedagogy: a new form of teaching with educacional proposols for sustentable development - Mário Jorge Cardoso Coelho Freitas; José Ramon Marón Lamadrid; Cátia Maria Machado da Costa Pereira; Hilda Gomes Dutra Magalhães (Universidade Estadual de Campinas, 2007)
A Ecopedagogia surgiu da necessidade dos tempos hodiernos de preservar o meio ambiente e buscar ações para a sustentabilidade. O objetivo deste artigo é discutir o surgimento da Ecopedagogia como subsídio norteador para as ações educativas que promovam a consciência ecológica e oriente a sociedade na educação para a sustentabilidade. Buscou-se o entendimento de educação e de sustentabilidade como sustentáculo da discussão, de forma a desvelar o pano de fundo da história evolutiva que permeia a Ecopedagogia. Ecopedagogy has risen from the needs of modern times in preserving the environment and to find means of sustentability. The aim of this article is to discuss the arising of Ecopedagogy as a guiding subsidiary for educative actions which will promote ecological awareness and orientate the society in sustainability education. Finding the means of acquiring an understanding of education and of sustainability as a sustenance for discussion, a form of unveiling the background of evolving history which has brought about Ecopedagogy.